2022
DOI: 10.1371/journal.pone.0277477
|View full text |Cite
|
Sign up to set email alerts
|

Rotenone causes mitochondrial dysfunction and prevents maturation in porcine oocytes

Abstract: Rotenone is a commonly used insecticidal chemical in agriculture and it is an inhibitor of mitochondrial complex Ⅰ. Previous studies have found that rotenone induces the production of reactive oxygen species (ROS) by inhibiting electron transport in the mitochondria of somatic and germ cells. However, there is little precise information on the effects of rotenone exposure in porcine oocytes during in vitro maturation, and the mechanisms underlying these effects have not been determined. The Cumulus-oocyte comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…A number of studies have shown that rotenone induces cell death along the path of mitochondrial-dependent apoptosis, increasing the number of apoptotic cells [ 25 , 56 , 57 ]. In the present study, the effect of diol and its epoxidized form on the survival of the neuroblastoma cell line SH-SY5Y exposed to rotenone was studied.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that rotenone induces cell death along the path of mitochondrial-dependent apoptosis, increasing the number of apoptotic cells [ 25 , 56 , 57 ]. In the present study, the effect of diol and its epoxidized form on the survival of the neuroblastoma cell line SH-SY5Y exposed to rotenone was studied.…”
Section: Discussionmentioning
confidence: 99%
“…Park and Koh (2020) and Wang et al (2021) discovered that rotenone treatment significantly enhanced the expression of LC3II and p62 in SH-SY5Y cells. In addition, Heo et al (2022) found increased levels of ubiquitin and LC3 expression in rotenone-exposed porcine oocytes. These findings aligned with our results.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, inhibition of complex II by malonic acid counteracted the effects of BBR and rotenone, suggesting that the activation of complex II as well as inhibition of complex I is involved in the action of BBR. Rotenone enhances ROS production by complex II [ 21 ], induces mitochondrial depolarization [ 22 ], increases mitophagy [ 23 ], and inhibits mitochondrial Fe 2+ oxidation, which results in cytotoxicity [ 24 ]. These suggest that the mitochondrial effects of BBR, like rotenone, are based on the inhibition of complex I.…”
Section: Discussionmentioning
confidence: 99%